Asexual sporulation facilitates adaptation: The emergence of azole resistance in Aspergillus fumigatus. (1st October 2015) - Zhang, Jianhua; Debets, Alfons J. M.; Verweij, Paul E.; Melchers, Willem J. G.; Zwaan, Bas J; Schoustra, Sijmen E.
Abstract: Understanding the occurrence and spread of azole resistance in Aspergillus fumigatus is crucial for public health. It has been hypothesized that asexual sporulation, which is abundant in nature, is essential for phenotypic expression of azole resistance mutations in A. fumigatus facilitating subsequent spread through natural selection. Furthermore, the disease aspergilloma is associated with asexual sporulation within the lungs of patients and the emergence of azole resistance. This study assessed the evolutionary advantage of asexual sporulation by growing the fungus under pressure of one of five different azole fungicides over seven weeks and by comparing the rate of adaptation between scenarios of culturing with and without asexual sporulation. Results unequivocally show that asexual sporulation facilitates adaptation. This can be explained by the combination of more effective selection because of the transition from a multicellular to a unicellular stage, and by increased mutation supply due to the production of spores, which involves numerous mitotic divisions. Insights from this study are essential to unravel the resistance mechanisms of sporulating pathogens to chemical compounds and disease agents in general, and for designing strategies that prevent or overcome the emerging threat of azole resistance in particular.